Human suffering and therapeutical adjustment contexts - Lúcar Vidal, Fredrik (2010)
The article is based on the relevance of having a cultural approach to psychological problems that occur nowadays. In that sense, we attempt to analyze what is the impact in a sychological level of some postmodern social phenomena such as anxiety for the happiness as a personal goal (rejection of all kinds of suffering), the huge increment of expectations and the excessive need for control. We do not deny nor underestimate other factors however we stress the importance of these. Likewise, according to the analysis proposed before, we will indicate the necessity in the implementation of Third Generation Behavior Therapy, as a reliable and also wel.researched path inside psychology, with special emphasis in Acceptance and Commitment Therapy (ACT), which is one of the most relevant psychotherapies for the treatment of these problems.